Penerapan pembelajaran problem posing untuk meningkatkan kemampuan berpikir kreatif siswa kelas VIII-1 SMP Negeri 23 Malang pada pokok bahasan bangun ruang sisi datar - Nela Wahyu Utami; Slamet Slamet (Universitas Negeri Malang, 2021)
This study aims to determine the process of applying problem posing learning that can improve the creative thinking skills of class VIII-1 students at SMP Negeri 23 Malang on the subject of polyhedron. This type of research is Classroom Action Research (CAR) which lasts two cycles. The instruments used in this study are validation sheets, observation sheets and test sheets. Based on the results of the study indicate that the application of problem posing learning with steps that include: the stage of apperception, the stage of delivering learning objectives, the stage of delivering motivation, the stage of understanding the material, the presentation stage, the stage of submission of questions, the stage of problem solving, and the conclusion phase creative class VIII-1 SMP Negeri 23 Malang on the subject of polyhedron with evidence in the first cycle there were 58.06 percent of students who reached the category of